Science Clubs: a Model to Inspire Youth (2019)
Science clubs have been very important over time, Felipe Zapata, an expert on the subject, reflects that you don't have to believe the myths that researchers aren't the only ones who can discover things. That is why young people and children who are interested in the search for new learning must be nurtured and the private enterprise is the one who sees the potential of science clubs and thus supports them financially.